Becoming part of me: Examining when objects, thoughts, goals, and people become fused with the self‐concept. Issue 1 (18th December 2017) - Hatvany, Thomas; Burkley, Edward; Curtis, Jessica
Abstract: Fusion refers to the sense that a construct is integrated into the self‐concept. When a person feels fused with a construct, there is a perceived "oneness" with the construct, and as a result, the construct is treated as an extension of the self. This concept of fusion has been explored across a wide range of constructs and within a number of subfields in psychology. The goal of this article is to provide a comprehensive view of the fusion process and to connect these disparate areas of literature underneath a single unifying theme. Specifically, we focus on five constructs that researchers have explored in terms of fusion: objects, thoughts, goals, significant others, and groups. In our review, we discuss the ways that fusion is typically measured and highlight the consequences that occur as a result of such fusion. We conclude by highlighting questions that remain unanswered and suggest potential areas of future development.